Direction of Trade Statistics Quarterly, March 2006. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2006)
This publication provides data on the country and area distribution of countries exports and imports as reported by themselves or by their partners. The quarterly issues cover data for the most recent six quarters and the latest year for 169 countries, and ten quarters and five years for the world and area tables.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: General Financial Markets; Investment Decisions; Portfolio Choice